¿Qué se debe a España? Dispute about the Importance of Spain in European Intellectual History - Černá, Jana (Dějiny – teorie – kritika, 2012)
This study deals with a debate about the importance of Spain in European intellectual history. The issue is treated on three levels. Firstly, it is seen as a political and social problem. Secondly, it is viewed as amethodological issue, and last but not least, it is seen as a product of so-called ‘black legend’ (leyenda negra). The text analyses the reasons which led to Spain being seen as backwards, non-modern, and incapable of taking an equal place among civilised European nations. It attempts to disentangle motivations behind the various particular claims about the importance of Spain in European history (or lack thereof ), demonstrating that the Spanish themselves largely contributed to a negative view of the Spanish nation in the course of trying to come to terms with the history of the Spanish nation and attempting a modernisation of their country. The study also highlights the existence of various prejudices and simplifications which are, in connection with the Spanish nation, deeply rooted not only in general consciousness but also refl ected in various academic works.